Opportunities to reduce cancer barriers: Community town halls and provider focus groups - Mosavel, Maghboeba (2012)
This paper presents the findings from town hall meetings held with community residents and focus groups with healthcare providers. A total of five town halls (N=139) were conducted. Four were conducted in English and a fifth was conducted in Spanish to obtain the input of the local Hispanic community. Surveys were provided to town hall participants to assess their perceptions of cancer and screening as well as their cancer screening behaviors. Participants were asked questions designed to determine local gaps and needs in health and cancer care, and their attitudes regarding breast cancer resources, education, treatment and clinical trials. Additionally, four focus groups (N=45) were held with a wide range of providers to obtain their perspectives on barriers to breast cancer screening, local cancer prevention and care, and clinical trials. Results indicate gaps in local resources and support services, particularly in terms of education and integrated care.